ANK3 Gene Polymorphism Rs10994336 Influences Executive Functions by Modulating Methylation in Patients With Bipolar Disorder - Tang, Lili; Liu, Juan; Zhu, Yue; Duan, Jia; Chen, Yifan; Wei, Yange; Gong, Xiaohong; Wang, Fei; Tang, Yanqing (Frontiers in Neuroscience, 2021)
Background: The identification of meQTLs (methylation quantitative trait loci) shed light on the interpretation of the function of genetic variants in noncoding regions. The intronic single nucleotide polymorphism rs10994336 within the ANK3 has emerged as one of the most replicated risk variants for bipolar disorder (BD) in genome-wide association studies. Whether rs10994336 functions as a meQTL to mediate the association between genotype and phenotype is remain unclear. Method: A total of 154 patients with BD and 181 healthy controls (HC) were recruited. The genotypes of rs10994336 and methylation levels of CpG sites within ANK3 were tested. Executive functions were assessed using a computerized version of the Wisconsin Card Sorting Test (WCST). Results: BD patients with the risk-T allele of rs10994336 scored lower on tests of executive function compared to homozygous CC carriers, after controlling for age, gender and education level. No significant difference was found in HC individuals. The risk-T allele is associated with a lower methylation level of CpG site cg02172182 in HC after multiple corrections and replicated in the BD group in the same direction. Further mediation analysis revealed that the cg02172182 methylation significantly mediated the association between the polymorphism rs10994336 and PE index of WCST in patients with BD. Conclusion: Our study suggests that BD related genetic variant rs10994336 in ANK3 impacts executive functions by modulating ANK3 methylation, supporting the methylation acts as a mediator between genotype and phenotype.